2014
DOI: 10.1007/s11033-014-3035-7
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and functional analysis of eugenol O-methyltransferase gene reveal metabolite shifts, chemotype specific differential expression and developmental regulation in Ocimum tenuiflorum L.

Abstract: Eugenol-O-methyltransferase (EOMT) catalyzes the conversion of eugenol to methyleugenol in one of the final steps of phenylpropanoid pathway. There are no comprehensive reports on comparative EOMT gene expression and developmental stage specific accumulation of phenylpropenes in Ocimum tenuiflorum. Seven chemotypes, rich in eugenol and methyleugenol, were selected by assessment of volatile metabolites through multivariate data analysis. Isoeugenol accumulated in higher levels during juvenile stage (36.86 ng g(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 39 publications
2
20
0
Order By: Relevance
“…The linalool compound in the samples of the control and the treatments was the main compound observed, varying between 46 and 55%, which is in accordance with the relative percentage of linalool obtained in samples from this cultivar during the flowering stage (Marotti et al, 1996). Regarding eugenol, Renu et al (2014) reported that there is a higher level of eugenol-o-methyltransferase (EOMT) transcripts during the juvenile and pre-flowering stage and that, conversely, a remarkable decrease of EOMT transcripts occurs during the post-flowering stages of several chemotypes, which indicates an extensive transcriptional reprogramming associated with decreased accumulation of the metabolites. Similarly, during the flowering stage, when the 2nd harvest was carried out, the essential oil samples presented relatively low amounts of methyleugenol and eugenol, which decreased from the 1st to the 2nd harvest, independent of the treatment applied.…”
Section: Quality Variation In Response To the Biotic And Abiotic Factorsupporting
confidence: 83%
“…The linalool compound in the samples of the control and the treatments was the main compound observed, varying between 46 and 55%, which is in accordance with the relative percentage of linalool obtained in samples from this cultivar during the flowering stage (Marotti et al, 1996). Regarding eugenol, Renu et al (2014) reported that there is a higher level of eugenol-o-methyltransferase (EOMT) transcripts during the juvenile and pre-flowering stage and that, conversely, a remarkable decrease of EOMT transcripts occurs during the post-flowering stages of several chemotypes, which indicates an extensive transcriptional reprogramming associated with decreased accumulation of the metabolites. Similarly, during the flowering stage, when the 2nd harvest was carried out, the essential oil samples presented relatively low amounts of methyleugenol and eugenol, which decreased from the 1st to the 2nd harvest, independent of the treatment applied.…”
Section: Quality Variation In Response To the Biotic And Abiotic Factorsupporting
confidence: 83%
“…Furthermore, eugenol synthase genes (EGS) have also been reported in some species such as Rose, Ocimum, and Gymnadenia [28,29,30]. The genes coding O -methyltransferases (EOMT) involved in methyleugenol have been isolated and functionally characterized in loquat ( Eriobotrya japonica ), Ocimum tenuiflorum , Clarkia breweri , sweet basil ( Ocimum basilicum ), and ripe apple fruit [31,32,33,34,35]. Cinnamyl alcohol dehydrogenase (CAD; EC 1.1.1.195), a member of alcohol dehydrogenase, functions in converting hydroxycinnamyl aldehydes to corresponding alcohols, the various direct precursors of lignin [36], among which the coniferyl alcohol also acts as the precursor in methyleugenol boosynthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Green forma of O. tenuiflorum showed high transformation frequency and leaves were the best among the explants in terms of both transformation efficiency and frequency. Though it is hard to explain as to why hairy roots developed more in green forma leaves, in an earlier study (Renu et al 2014) it was observed that green plants accumulated more signaling phenolics like phenylpropenes whereas red plants accumulated more anthocyanins. These phenylpropenes, like acetosyringone might influence more hairy root formation in the green forma.…”
Section: Resultsmentioning
confidence: 97%
“…The red forma accumulates the pigment anthocyanin that is very reactive towards most reactive oxygen species (ROS) because of their electron deficiency (Galvano et al 2004) and thus contributes towards health promoting properties as potent antioxidants. Both red and green forma plants harbor a wide diversity of volatile essential oils rich in phenylpropanoids and terpenoids (Jirovetz et al 2003;Renu et al 2014). These metabolites individually or in combination impart aroma, fragrance, UV protection and have important roles in plant defence or serve as signal molecules between plants and microbes (Viña & Murillo 2003).…”
Section: Introductionmentioning
confidence: 99%